Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Guru SMA Negeri 1 Kintom: The Influence of Work Motivation and Work Environment on the Performance of Teachers at SMA Negeri 1 Kintom - Pikson Lenggetio; Sri Rahayu Husen (Jurnal Ilmiah Produktif, 2026)
The research approach used in this study is a quantitative approach. The sample consisted of 27 respondents. The type of data used in this study is primary data. Data collection techniques were carried out by distributing questionnaires to teachers at SMA Negeri 1 Kintom. The data analysis technique used was multiple linear regression analysis with the equation Y = 2.854 + 0.414 + 0.335. Work motivation has a significant effect on teacher performance, with a t-value of 1.840 compared to a t-table value of 1.71, and a significance value of 0.003 ≤ 0.05. This indicates that partially, work motivation significantly influences teacher performance. The work environment shows a t-value of 2.209 compared to a t-table of 1.71, with a significance value of 0.002 ≤ 0.05, indicating a significant partial effect on teacher performance. The correlation coefficient for work motivation is 0.211 (low), while the work environment is 0.425 (moderately strong).